Reclaiming the Philosopher-King’s Wisdom: Reconciling Ethiopia’s Imperial, Derg, and Ethnic Federalist Actors toward a Durable Peace - Belay Sitotaw Goshu; Muhammad Ridwan (Polit Journal Scientific Journal of Politics, 2026)
Ethiopia’s political history has been shaped by the philosopher‑king ideal, a divinely sanctioned, wise ruler modelled on King David and legitimated by the Kebra Nagast and the Orthodox Church. This ideal collapsed under feudal oppression, imperial neglect during the 1973–74 Wollo famine, and the 1974 revolution. This study investigates how the ethical core of the philosopher‑king model (justice, wisdom, service) can be reclaimed to reconcile Ethiopia’s three competing political legacies: Imperial, Derg, and Ethnic Federalist. Methods: A historical‑institutional analysis integrated with peacebuilding theory was employed. Qualitative interpretation of primary sources (Kebra Nagast, constitutions, and policy documents) and secondary literature (transitional justice reports, conflict analyses) informed the framework. The imperial legacy offers national unity but rests on feudal hierarchy; the Derg’s revolutionary rupture destroyed the old order but produced terror and famine; ethnic federalism institutionalized division, culminating in the Tigray War (2020–2022) and ongoing violence. The ethical attributes of King David protective justice (Psalm 72), repentant humility (2 Samuel 12), and covenantal unification (2 Samuel 5) provide normative resources that can be extracted from theocratic monarchy and embedded in democratic institutions. Conclusion: Reconciliation requires neither imperial restoration nor revolutionary erasure, but a new social contract inspired by Davidic wisdom, applied through inclusive national dialogue, land and economic reforms, tiered transitional justice, and multiperspective education. Recommendation: Implement a truth‑healing commission that includes all three actors, soften ethnic federalism through constitutional reform, and foster a civic, non‑ethnic national identity.